STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU DI TK PERTIWI 01 PATI - Nur Khotimah; Desty Irnayanty; Lita Latiana (AlBanna: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research have purpose to describe the principal’s strategy to increase teacher skill at TK Pertiwi 01 Pati. This research metode used deskriptif qualitativ. This data collection tool uses observation, interview and documentation. Result of this research show that principal’s strategy to increase teacher skill is : 1) pedagogic aspect: done by giving guidance and supervition to teacher related to learning. 2) personality aspectis doing by gave motivation and good act for teacher to do the best for student and the progess of institution. 3) Sosial aspect doing by created sense of togetherness and harmony with improve communication between the teacher’s so as to create a harmonis atmosphere in the school inveronment. 4) Carried by the teacher supervisor in disiplin, involued the teacher in workshop, training, seminar, mover teacher program and next S2 for knowledge expansion to increase the students quality of students. Carry out supervision of teacher performance to evaluated the teacher perform and increase the quality.